Determinan Penggunaan Rokok Elektrik (Vape) pada Kalangan Remaja di Indonesia - Wirajaya, Karma; Farmani, Putu Ika; Laksmini, Putu Ayu (LPPM Hang Tuah Pekanbaru, 2024)
Vaping is a form of changing conventional cigarettes into electronic cigarettes. Since 2014, the distribution of e-cigarettes throughout the world has become a trend and has reached various groups of consumers. In Indonesia, e-cigarette users continue to increase every year. GATS (Global Adult Tobacco Survey) findings in 2021 submitted by the Ministry of Health of the Republic of Indonesia found that there was an increase in the prevalence of e-cigarette users up to 10 times compared to the last survey in 2011, from 0.3% to 3% including in the world is increasing, especially in teenagers. This research aims to determine the determinants of electronic cigarette (vape) use among teenagers in Indonesia. This research uses a systematic literature study through searches using the Google Scholar site. The inclusion criteria are the article has been published in a journal, explains the factors of electronic cigarette/vape use among teenagers and the article can be downloaded while the exclusion criteria is the article only form an abstract. Based on these criteria, 13 articles were obtained. As a result, several factors influence the use of electronic cigarettes (vape) among teenagers in Indonesia. These factors include knowledge, perception of e-cigarettes, support from friends and family, cigarette information/advertisement, ease of access to e-cigarettes, price of e-cigarettes, and lifestyle influencing adolescent behavior in using e-cigarettes (vape). There needs to be a policy from the government to regulate the use of e-cigarettes in Indonesia.